2013
DOI: 10.1371/journal.pone.0052669
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Basis for Predicting Technological Progress

Abstract: Forecasting technological progress is of great interest to engineers, policy makers, and private investors. Several models have been proposed for predicting technological improvement, but how well do these models perform? An early hypothesis made by Theodore Wright in 1936 is that cost decreases as a power law of cumulative production. An alternative hypothesis is Moore's law, which can be generalized to say that technologies improve exponentially with time. Other alternatives were proposed by Goddard, Sinclai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
188
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 207 publications
(215 citation statements)
references
References 21 publications
7
188
0
Order By: Relevance
“…Following the work of Griliches 42 , others evaluated patenting in the energy sector, and concluded that patents are a valid indicator to measure innovativeness within the energy sector 2,28 . This result has been extended and re-confirmed by a number of authors 43 . PCT patent reviews contain high-quality standards and innovators seeking international protection file for PCT patents, attesting to the high economic value of their patent, which represents a gold standard for patent information 44 .…”
Section: Methodssupporting
confidence: 71%
“…Following the work of Griliches 42 , others evaluated patenting in the energy sector, and concluded that patents are a valid indicator to measure innovativeness within the energy sector 2,28 . This result has been extended and re-confirmed by a number of authors 43 . PCT patent reviews contain high-quality standards and innovators seeking international protection file for PCT patents, attesting to the high economic value of their patent, which represents a gold standard for patent information 44 .…”
Section: Methodssupporting
confidence: 71%
“…It will take many years of machine learning and many more miles than anyone has logged of both simulated and real-world testing to achieve the perfection required for Level 5 autonomy." (Pratt, 2017) Simultaneously, research on technology improvement across industries suggests that there is a power-law relationship between production and performance: A doubling of production leads to a constant improvement in performance (as measured by cost or other characteristics) (Nagy et al, 2013). A similar relationship may exist for the performance of machine learning algorithms and data sets (Sun et al, 2017).…”
Section: What Does the Evidence Suggest About The Conditions That Leamentioning
confidence: 99%
“…My analyses of 30 or more years of data [2][3][4] show that the costs of Back the renewables boom Low-carbon technologies are getting better and cheaper each year, but continued public-policy support is needed to sustain progress, says Jessika E. Trancik.…”
Section: Rapid Innovationmentioning
confidence: 99%
“…Some technologies are more open to improvement than others [2][3][4][5][6][7] . Compact, modular systems, such as photovoltaics and electronics, are easily experimented on 5,7 .…”
Section: Rapid Innovationmentioning
confidence: 99%
See 1 more Smart Citation